Plasma immersion ion implantation and shot peening influence on the fatigue strength of AA 7050-T7451 aluminum alloy - Bastos, Yara Coelho [UNESP] (2020)
The 7xxx aluminum alloy series is applied in aircraft components that demand high specific mechanical strength and fatigue resistance. The corrosive environment and friction forces imposed on those components reduce the service life. Therefore, anodizing is frequently used to enhance resistance against corrosion and wear. However, anodizing decreases the fatigue life of aluminum alloys. Plasma immersion ion implantation (PIII) is an alternative surface treatment that has been used to improve surface hardness, corrosion resistance and reduce wear damage. The PIII treatment consists of accelerating positive ions towards a sample by applying negative high voltage pulses in plasma. The shot peening (SP) process is a surface treatment that can be used with other surface treatments to improve the fatigue strength. The present work aimed at investigating the fatigue behavior of AA 7050-T451 aluminum alloy treated with SP, PIII, and a combination of both SP and PIII surface treatments. The combination of SP and PIII treatments(SP + PIII)improved the fatigue performance with respect to the base material and was more efficient than PIII in improving the fatigue strength for high-cycle fatigue regime. The fatigue strength improvement is related to the induced compressive residual stresses at the surface layers, which was responsible for delaying the nucleation and early fatigue crack propagation periods. The residual stress at the surface changed from -62 MPa to -130 MPa and -210 MPa for the SP and SP + PIII conditions, respectively. Compared to chromic anodizing, the SP + PIII condition increased the fatigue life in about 4 times at a maximum stress level of 281 MPa. The combination of SP and PIII treatments tested in this work is more advantageous regarding fatigue behavior than chromic anodizing, which reduces the fatigue strength of the material.